MARKET ORIENTATION AS THE APPROPRIATE APPROACH FOR SMEs IN DEALING WITH EXTERNAL ENVIRONMENTAL FACTORS - Situmorang, James (Advances in Social Sciences Research Journal, 2019)
Since it first appeared in 1990, market orientation has been a research topic that is popular among academics until present time. Market orientation can be divided into two categories, cultural approach according to Narver & Slater and behavioral approach according to Jaworski & Kohli. Market orientation by Narver & Slater is widely used by market orientation researchers at the SME level. UKM as a business unit cannot be separated from its external environmental factors. External environmental factors according to Kohli & Jaworski are market turbulence, technological turbulence, and the competitive intensity. Some studies measure the effect of market orientation on company performance that includes external environmental factor variables. The results of the study generally indicate that market orientation and external environmental factors positively affect the company performance. Thus, market orientation is the appropriate approach for SMEs in dealing with external environmental factors Keywords: Market orientation, external environment factor, customer orientation, competitor orintation, inter-functional coordination, market turbulence, technology turbulence, competitive intensity.